Encoding Schemes for Reducing Transition Activity and Power Consumption in VLSI Interconnects-A Review - N, Vithyalakshmi.; P, Nagarajan; Kumar.N, Ashok; G.S, Vinoth. (International Journal of Engineering and Technology, 2018)
Low power design is a foremost challenging issue in recent applications like mobile phones and portable devices. Advances in VLSI technology have enabled the realization of complicated circuits in single chip, reducing system size and power utilization. In low power VLSI design energy dissipation has to be more significant. So to minimize the power consumption of circuits various power components and their effects must be identified. Dynamic power is the major energy dissipation in micro power circuits. Bus transition activity is the major source of dynamic power consumption in low power VLSI circuits. The dynamic power of any complex circuits cannot be estimated by the simple calculations. Therefore this paper review different encoding schemes for reduction of transition activity and power dissipation.Â